PROMOSI DALAM UPAYA MENINGKATKAN PENGETAHUAN KUALITAS TIDUR PADA PELAJAR SMA - Hendrati, Lucia Yovita; Fitriyah, Nurul; Farapti, Farapti (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
Sleep quality has an important role in health. High school students can to maintain good concentration , because it needed in learning process. Therefore, the student must know to keep good sleep of quality. The initial survey showed that most of the students at SMA Muhamaddiyah 10 Surabaya had poor sleep quality (60%). The purpose of this community service activity is to transfer knowledge about sleep mechanisms and sleep stages. The activity method is an initial survey about sleep quality, the second step is to conduct a pre test. The third step is promotion in the form of material presentations and discussions. The next step is to hold a quiz whose contents are the results of a survey about student problems that interfere with sleep quality and the ways students choose to overcome them. The final step is to do an evaluation in the form of a post test. The number of students from SMA Muhamadyah 10 Surabaya was 20 students who were involved in the activity. Students in this activity were very enthusiastic about discussing the sleep problems they experienced. The evaluation results showed a change in knowledge about sleep quality. The results of the pre-test showed that knowledge of the questions that were answered correctly between 75% - 85% increased after giving the material to 85% - 100%.